Advanced Glycation End Products Activate the miRNA/RhoA/ROCK2 Pathway in Endothelial Cells. (February 2014) - Wu, Xiao‐dan; Liu, Wei‐lin; Zeng, Kai; Lei, Hong‐yi; Zhang, Qing‐guo; Zhou, Shu‐qin; Xu, Shi‐yuan
Abstract Objective AGEs induce endothelial cell dysfunction in HUVECs, resulting in ROS production and triggering apoptosis. This study sought to identify miRNAs involved in AGE‐induced endothelial cell injury. Methods Microarray analysis to identify miRNAs altered with AGE stimulation was undertaken, and results were confirmed using real‐time quantitative polymerase chain reaction. The interaction of miRNAs with the RhoA and ROCK2 genes was confirmed using luciferase assays, and their effects on expression were determined using Western blot analysis. The effects of AGEs and miRNAs on endothelial cell permeability were assessed. Results AGEs induced ROS production and apoptosis of HUVECs (p < 0.05). AGE‐induced miR‐200b and miR‐200c downregulation led to increased expression of their target genes, RhoA and ROCK, respectively. AGE‐induced endothelial cell permeability and F‐actin expression were significantly reduced with both miR‐200b and miR‐200c mimics (p < 0.05). Furthermore, AGE‐induced stress fiber formation was reduced in cells treated with miR‐200b mimics. Conclusion miR‐200b and miR‐200c are suppressed in AGE‐induced endothelial cell injury, resulting in unregulated RhoA/ROCK2 signaling. Further studies are necessary to evaluate the therapeutic value of targeting miRNAs or their target genes for treatment of vascular diseases.